Exploring the effects of COVID-19 restrictions on wellbeing across different styles of lockdown. Issue 1 (27th April 2022) - Ingram, Joanne; Hand, Christopher J.; Hijikata, Yuko; Maciejewski, Greg
Countries have instigated different restrictions in response to the COVID-19 pandemic. For instance, nationwide, strict "lockdown" in Scotland was enacted with breaches punishable by law, whereas restrictions in Japan allowed for travel and interaction, with citizens requested rather than required to conform. We explored the impact of these differential strategies on health behaviours and wellbeing. In February 2021, 138 Scottish and 139 Japanese participants reported their demographic information, pandemic-induced health behaviour-change (alcohol consumption, diet, perceived sleep quality, physical activity), negative mood, and perceived social isolation. Scottish participants' health behaviours were characterised by greater change (typically negative), most likely due to greater lifestyle disruption, whereas Japanese participants' behaviours were more-stable. Negative changes to health behaviours were typically associated with poorer mental wellbeing and isolation. Interestingly though, Japanese participants reported greater negative mood but not isolation despite the less-restrictive lockdown. Taken together, different lockdown styles led to different changes in health behaviours.